Qabil dan Habil Kisah orang-orang zhalim Syeikh Thoha Abdur Rauf Saad Hasan Muhammad Ali ; penerjemah, Jujuk Najibah Ardianingsih ; penyunring A : Choiran Marzuki - SAAD, Thaha AbdurRauf, Syeikh; Ali Saad Hasan Muhammad; Ardianingsih, Jujuk Najibah; Marzuki, A. Khoiran (Mitra Pustaka, 2004)
384 hlm 21 cm